A Collaborative Approach to Describe the Domain Language through the Language Extended Lexicon - Antonelli, Rubén Leandro (2016)
Software development is a succession of descriptions in different languages in which every description is based on a previous one. Since the requirements specification is one of the first descriptions, it is important to begin software development with requirements that are as correct and as complete as possible. Although some literature holds the belief that correctness and completeness are two attributes that requirements specifications must satisfy, we know that these attributes are very difficult to meet. However, we have to find ways to diminish the level of incompleteness and deal with the possible conflicts that do arise in the requirements context. Defining the domain language before specifying the requirements is a way of coping with these problems. Nowadays, software systems involve many stakeholders and it is hard to engage all of them to produce a domain language specification. We rely on collaboration to foster the involvement and cooperation of the stakeholders, thus they are able to explore the differences constructively and provide a common understanding of the domain language beyond their own limited views. In this paper, we propose a strategy to capture the domain language in a collaborative way using the Language Extended Lexicon and we show a validation of the proposed strategy.